Physicochemical fundamentals of processing solutions of thermoplastic poly(ether urethane)s to obtain fibrous-porous polymer composite materials - G. M. Kovalenko; E. S. Bokova; N. V. Evsyukova (Тонкие химические технологии, 2023)
Objectives. To study the structure and properties of solutions of thermoplastic poly(ether urethane)s (PEUs) to inform their potential use in the production of fibrous-porous polymer composite materials with a given structure and set of performance properties depending on the field of practical application.Methods. The composition of PEUs was studied by attenuated total reflection infrared (ATR-IR) spectroscopy using a program for correcting the spectra on an IR Fourier spectrophotometer, as well by differential scanning calorimetry (DSC) using a heat flow calorimeter. The viscosity of PEU solutions was determined on a rotational viscometer.Results. The chemical composition of PEUs and the nature of the formation of hydrogen bonds were studied. An analysis of the spectra demonstrates the almost complete identity of the PEUs synthesized from the same 4,4'-diphenylmethane diisocyanate. In the studied PEUs of the Vitur and Desmopan® brands, as well as Sanpren, pronounced absorption bands characteristic of urethane groups involved in the formation of hydrogen bonds are visible in the region from 1702 to 1730 cm−1. The temperature transitions and thermal stability of the investigated PEUs were determined by DSC. The influence of the ratio of rigid and flexible blocks, as well as the nature of hydrogen bonds on the melting temperatures of polymers, was shown. Analysis of the DSC curves demonstrated all the studied PEUs to have high melting points ranging from 159 to 215°C. From the studied temperature dependences of the structural viscosity of thermoplastic PEUs solutions, all solutions were established to have a minimum viscosity anomaly; the value of the logarithm of viscosity depends on the chemical composition and structure of the initial PEUs. It is shown that the viscosity anomaly of PEU solutions can be reduced with increasing temperature.Conclusions. A comparison of the chemical composition, structure, thermal and rheological characteristics of thermoplastic PEUs with PEU solutions widely used for the production of fibrous-porous materials and coatings of Sanpren LQ-E-6 and Vitur R 0112 grades demonstrates their practicability as production materials and coatings having a predetermined structure and a set of properties depending on the requirements and operating conditions of finished products.